2017
DOI: 10.4168/aair.2017.9.6.509
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sensitization to Mold and Impaired Pulmonary Function in Children With Asthma

Abstract: PurposeRecent data indicate that sensitization to mold contributes to the severity and persistence of asthma. In this study, we investigated the relationships between sensitization to mold and lung function parameters in children with asthma.MethodsWe retrospectively reviewed clinical data from 551 asthmatic subjects. We selected subjects who met clinical diagnostic criteria of asthma. Their spirometry, methacholine challenge tests, and measurements of blood eosinophils, serum IgE, eosinophil cationic protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Approximately 12.2% of children with persistent asthma are sensitized to molds (33). There is a wide variety of indoor and outdoor molds and its allergenic proteins vary by mold species.…”
Section: Environmental Factors In the Management Of Childhood Asthmamentioning
confidence: 99%
“…Approximately 12.2% of children with persistent asthma are sensitized to molds (33). There is a wide variety of indoor and outdoor molds and its allergenic proteins vary by mold species.…”
Section: Environmental Factors In the Management Of Childhood Asthmamentioning
confidence: 99%
“…24,95,96 Frequency of sensitization and degree of skin-test positivity to Alternaria has been strongly linked to asthma severity, and exposure in those sensitized is associated with more frequent severe and life-threatening episodes of asthma. 98 There was no difference between the two groups in terms of incidence of rhinitis or eczema, FENO or blood eosinophil levels, suggesting the relationship between fungal sensitization and STRA is not merely due to increased atopic tendency. 98 There was no difference between the two groups in terms of incidence of rhinitis or eczema, FENO or blood eosinophil levels, suggesting the relationship between fungal sensitization and STRA is not merely due to increased atopic tendency.…”
Section: Mouldsmentioning
confidence: 79%
“…67,96,97 A study of 566 children with asthma in South Korea found those sensitized to mould compared with those sensitized to other aeroallergens but not mould had significantly lower lung function and increased airway hyperresponsiveness. 98 There was no difference between the two groups in terms of incidence of rhinitis or eczema, FENO or blood eosinophil levels, suggesting the relationship between fungal sensitization and STRA is not merely due to increased atopic tendency. A similar study showed those sensitized to moulds compared with those sensitized to other aeroallergens but not moulds had a significantly lower FEV 1 and were more likely to have STRA, suggesting moulds may play a greater role in STRA than other aeroallergens.…”
Section: Mouldsmentioning
confidence: 79%
See 1 more Smart Citation
“…The most common species to which children are sensitized and exposed are Alternaria and Cladosporium (outdoor), Aspergillus and Penicillium (indoor) 43 . The prevalence of mold sensitization in children with persistent asthma is variable in the literature -ranging from 12% to 66% 44,45 . Qualitative assessments of fungal exposure in the form of mildew odor or visible mold have been linked to increased risk of allergic rhinitis and asthma 46 .…”
Section: Rodents (Mouse)-mentioning
confidence: 99%